Aplicación del deterioro en la planta productora de las pymes del sector bananero del cantón Machala. - Pesantez Chinchilima, Gissella Beatriz (Machala : Universidad Técnica de Machala, 2024)
The purpose of this work is to investigate the application of the impairment of the production plant of small and medium-sized companies in the banana sector in the city of Machala, in order to emphasize the importance of recording the impairment in the financial statements of the entities, which are subsequently submitted to the Superintendence of Companies and in turn determine the impact of the impairment of the plant in the financial statements. In order to comply with everything described above, a positivist paradigm was designed, under a descriptive quantitative approach, under a deductive method, the application of the impairment of the production plant account of the property, plant and equipment subgroup within the financial statements of the companies was disclosed. Through the study carried out, it was determined that the companies do not apply the impairment of the production plant; however, there are biological assets within the companies and therefore they apply the impairment to them. The same items and procedures were found in the statement of financial position, income statement and explanatory notes. There is a shortage of procedures for production plant, impairment of property, plant and equipment, biological assets and impairment of biological assets in the explanatory notes. The impact of impairment on the results of small and medium-sized companies is very low. In conclusion, it is determined that the companies do not apply the impairment of the production plant within the financial statements, therefore, it is important to calculate the impairment within the banana companies and record them in the financial statements to have a better control by applying the corresponding regulations for impairment, property, plant and equipment and agriculture described in the IFRS for SMEs, which are of utmost importance for the regulatory bodies.
Este trabajo tiene como propósito investigar la aplicación del deterioro de la planta productora de las pequeñas y medianas empresas del sector bananero de la ciudad de Machala, con el fin de recalcar la importancia de registrar el deterioro en los estados financieros de las entidades, mismas que posteriormente se presentan a la Superintendencia de Compañías y a su vez determinar el impacto del deterioro de la planta en los estados financieros. Para cumplir con todo lo descrito anteriormente, se diseñó un paradigma positivista, bajo un enfoque cuantitativo de carácter descriptivo, bajo un método deductivo se dio a conocer la aplicación del deterioro de la cuenta planta productora del subgrupo de propiedad, planta y equipo dentro de los estados financieros de las empresas. A través del estudio realizado se determinó que las empresas no aplican el deterioro de la planta productora, sin embargo, existe el activo biológico dentro de las empresas por lo cual aplican el deterioro a los mismos. Mismo rubros y procedimientos fueron encontrados dentro del estado de situación financiera, estado de resultados y las notas aclaratorias. Existe una escasez de procedimientos de planta productora, deterioro de propiedad planta y equipo, activos biológicos y deterioro de activo biológico dentro de las notas aclaratorias. El impacto que tiene el deterioro dentro de los resultados de las pequeñas y medianas empresas es un impacto muy bajo. En conclusión, se determina que las empresas no aplican el deterioro de la planta productora dentro de los estados financieros, por ende, es importante calcular el deterioro dentro de las empresas bananeras y registrarlos en los estados financieros para llevar un mejor control aplicando las normativas correspondientes deterioro, propiedad, planta y equipo y agricultura descritas en las NIIF para las Pymes mismas que son de suma importancia para los organismos reguladores.
Keywords: DETERIORO; PLANTA PRODUCTORA; ACTIVO BIOLOGICO; PROPIEDAD